BEHAVIORAL BIASES AND CREDIT CARD REPAYMENTS AMONG MALAYSIANS - Fazelina Sahul Hamid; Siti Haslina Md Harizan (The International Journal of Banking and Finance, 2023)
Analyses done using the survey response of 451 credit cardholders in the northern region of West Malaysia have shown that credit cardholder repayment pattern differed based on their demographic profile. Specifically, the study found that credit cardholders who were younger and earned a lower income tended to make poorer repayment decisions. In contrast, those with higher academic qualifications tended to make better repayment decisions. Further analyses also revealed that behavioral biases were better at predicting those who made full payment of the outstanding balance and those who paid more than the minimum amount, but failed to predict those who only paid the minimum amount or less. In addition, it was found that overspending emerged as the strongest predictor which discriminated among the three repayment groups, followed by risk aversion, myopia and impulsiveness.